2020
DOI: 10.1101/2020.06.19.20135962
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Methadone and Suboxone® mentions on Twitter: Thematic and Sentiment Analysis

Abstract: Background: Methadone and buprenorphine-naloxone (Suboxone®)have been discussed and compared extensively in the medical literature as effective treatments for opioid use disorder (OUD). While the evidence basis for the use of these medications is very favorable, less is known about the perceptions of these medications within the general public. Objective: This study aimed to use social media, specifically Twitter, to assess the public perception of these medications, and to compare the discussion content betwe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In a recent study using tweets as data to assess how the public perceives MOUD, Chenworth and her associates (2020) studied only treatments involving methadone or Suboxone, comparing the two, and found that despite the recognized effectiveness of these treatments, the people submitting the tweets did not communicate much about the benefits of treatment. The authors suggested that the stigmatization of people in treatment by tweeters might result in underutilization of MOUD.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study using tweets as data to assess how the public perceives MOUD, Chenworth and her associates (2020) studied only treatments involving methadone or Suboxone, comparing the two, and found that despite the recognized effectiveness of these treatments, the people submitting the tweets did not communicate much about the benefits of treatment. The authors suggested that the stigmatization of people in treatment by tweeters might result in underutilization of MOUD.…”
Section: Discussionmentioning
confidence: 99%